Sex differences in cancer and immunotherapy outcomes: the role of androgen receptor - Zhao, Junzhe; Wang, Qian; Tan, Alexandra F.; Loh, Celestine Jia Ling; Toh, Han Chong (Frontiers in Immunology, 2024)
Across the wide range of clinical conditions, there exists a sex imbalance where biological females are more prone to autoimmune diseases and males to some cancers. These discrepancies are the combinatory consequence of lifestyle and environmental factors such as smoking, alcohol consumption, obesity, and oncogenic viruses, as well as other intrinsic biological traits including sex chromosomes and sex hormones. While the emergence of immuno-oncology (I/O) has revolutionised cancer care, the efficacy across multiple cancers may be limited because of a complex, dynamic interplay between the tumour and its microenvironment (TME). Indeed, sex and gender can also influence the varying effectiveness of I/O. Androgen receptor (AR) plays an important role in tumorigenesis and in shaping the TME. Here, we lay out the epidemiological context of sex disparity in cancer and then review the current literature on how AR signalling contributes to such observation via altered tumour development and immunology. We offer insights into AR-mediated immunosuppressive mechanisms, with the hope of translating preclinical and clinical evidence in gender oncology into improved outcomes in personalised, I/O-based cancer care.